Cyclophosphamide in frequent-relapsing or steroid-dependent nephrotic syndrome: Review of 38 patients - Yulia Iriani; Taralan Tambunan; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 2005)
Background Steroid-sensitive nephrotic syndrome (SSNS) in chil-dren is characterized by relapsing courses in a substantial propor-tion of affected individuals. Children with frequent-relapsing neph-rotic syndrome (FRNS) or steroid-dependent nephrotic syndrome(SDNS) are at risk of severe steroid toxicity and need individual-ized treatment. Previous studies have elucidated that cyclophos-phamide (CPA) reduced the risk of relapses and increased thelength of subsequent remissions in children with relapsing SSNS.Methods This retrospective study evaluated 38 patients (26 FRNSand 12 SDNS) after cyclophosphamide therapy to elucidate theefficacy of CPA in FRNS or SDNS in the Department of Child Health,Cipto Mangunkusumo Hospital. All patients were treated with CPA(2 mg/kg per day) for 8 weeks, in combination with prednisone.Results The median (range) duration of follow up was 45 months(24-140 months) for FRNS and 29 months (24-63 months) forSDNS. The mean relapse rate one year prior to CPA therapy inFRNS and SDNS were 3.8 relapses/year (95%CI 3.4; 4.2) and 4.0relapses/year (95%CI 3.3; 4.7), which were reduced to 1.6 relapses/year (95% CI 1.1; 2.1) and 2.3 relapses/year (95%CI 1.5;3.2), re-spectively. The overall rate of cumulative sustained good response(complete remission or infrequent relapses) was 65% after 36months. Frequent relapsing versus steroid-dependent status wassignificantly correlated with rate of sustained good response after36 months (85% versus 15%) with OR=23 (95%CI 3.1;225.2).Conclusion The efficacy of cyclophosphamide therapy in themanagement of FRNS is better than in SDNS